Case studies of formative assessment practices : grade four English language teachers' practice, understanding and experiences. - Bhoola, Shayna Devi (My University, 2015)
Studies have shown that the practice of formative assessment is a challenge to many teachers. Teachers are either entrenched in their old habits and methods of assessment or they have not been adequately trained to apply formative assessment in the instructional process. It has been argued that formative assessment can raise standards and improve learners’ poor performances (Black and William, 2001). This study explored Grade 4 English language teachers’ practice of formative assessment: their understanding, practice and experiences within the micro-level of classroom instruction. Within the case study method data were collected through observations, interviews and document analyses. Bernstein’s (1996) concept of framing of evaluative criteria as operationalized by Morais (2002) framed the analyses of data in the study. The results showed that: three out of the four teachers were not conversant with formative assessment; they lacked the skills in effectively using evaluative criteria in the instructional context. The teachers’ conceptualization of transmission of evaluative criteria corresponded to weak framing. Thus their control of communicating the evaluative criteria by way of the lesson objectives, feedback and transmission of the knowledge were tacit. Those teachers were trained in South Africa, one teacher in the Apartheid Era while the other two were trained post-Apartheid. The fourth teacher, a Zimbabwean, and educated in Zimbabwe, was able to explain and practice formative assessment to a greater extent. Her control over communicating the evaluative criteria of lesson objectives and feedback within the context of instruction were strongly framed. Other factors inhibiting the three teachers from effectively using formative assessment, could be, large classes and insufficient time. The Zimbabwean teacher, however, was exposed to the same classroom constraints.